The "Cameos of Care Homes" project – care home staff's Vanguard involvement and reflections. Issue 2 (3rd May 2019) - Harris, Jess; Manthorpe, Jill
Abstract : Purpose: The Cameos of Care Homes project is an opportunity to use the medium of film to showcase the experiences and reflections of frontline care home staff whose employers participated in the National Health Service (NHS) England Vanguard programme. Reflecting on their involvement in one of the Enhanced Health in Care Homes Vanguards, 12 staff describe, in front of the camera, the impact on themselves and their colleagues, on their care for their older residents, and on the wider culture of the care home. The paper aims to discuss this initiative. Design/methodology/approach: The paper reports the experiences of care home staff that were purposefully recorded on film about their participation in a care home Vanguard. The recruitment of the care homes and staff is described, as are the development of interview questions and approaches needed when filming is considered as a research method. Findings: Participating care home staff reported that their involvement in the Vanguard programme had improved knowledge, confidence, morale, communication skills and the homes' learning cultures. They were enthusiastic about reporting their experiences on film. Examples were given of proactive early support from local NHS staff leading to improvements in care, thereby reducing demand on the NHS. However, participation was resource intensive for care homes. Care home staff hoped the support that accompanied the Vanguard programme would continue but were uncertain to what degree this would happen once the Vanguard programme ceased. Research limitations/implications: The interviews were undertaken with a self-selecting group of care home staff from two care homes operating in one of the six Vanguard sites in England. By their very nature, interviews for a public film cannot provide anonymity. Practical implications: Researchers seeking the views of care home staff may wish to consider filming interviews and presenting the film as a research output that is engaging and informative for care home and wider audiences. Originality/value: The paper presents an analysis of filmed interviews with care home managers and care workers working with older people. Their views on the Vanguard initiative have not been widely considered, in contrast to the sizeable literature relating to NHS activity and expenditure.